Association between blood pressure and BMI with bladder cancer risk and mortality in 340, 000 men in three Swedish cohorts. (16th January 2021) - Teleka, Stanley; Jochems, Sylvia H. J.; Häggström, Christel; Wood, Angela M.; Järvholm, Bengt; Orho‐Melander, Marju; Liedberg, Fredrik; Stocks, Tanja
Abstract: Background: The relation between obesity, blood pressure (BP) and bladder cancer (BC) risk and mortality remains unclear, partially due to potential confounding by smoking, the strongest risk factor for BC, and not accounting for tumor stage and grade in such studies. We investigated body mass index (BMI) and BP in relation to BC risk by stage and grade, and BC‐specific mortality, including separately among never‐smokers aimed at minimizing confounding by smoking. Methods: We analyzed 338, 910 men from three Swedish cohorts, with 4895 incident BC's (940 among never‐smokers) during follow‐up. Cox regression was used to calculate hazard ratios (HR) and 95% confidence intervals adjusted for smoking status. HRs for BMI and BP were corrected for their regression dilution ratios, calculated from 280, 456 individuals with 758, 641 observations. Results: Body mass index was positively associated with non‐muscle invasive BC (NMIBC, HR per 5 kg/m 2, 1.10 [1.02–1.19]) and NMIBC grade 3 (HR 1.17 [1.01–1.34]) in the full cohort, with similar effect sizes, albeit non‐significant, among never‐smokers. Systolic BP was positively associated with muscle‐invasive BC (MIBC, HR per 10 mmHg, 1.25 [1.00–1.55]) and BC‐specific mortality (HR 1.10 [1.01–1.20]) among never‐smokers, with weaker and non‐significant associations in the full cohort. Conclusions: In an analyses of BMI, BP and BC risk by stage and grade among men, we found modest positive associations between BMI and NMIBC and NMIBC grade 3. SBP was positively associated with MIBC and BC‐specific mortality in an analysis of never‐smokers, which may reflect the association, un‐confounded by smoking, also in a broader population. Abstract : The relationships between blood pressure body (BP) mass index (BMI) and bladder cancer (BC), have shown conflicting results in previous studies, this may be due to the mixing effect of smoking in such associations and not taking into account BC characteristics. In our study of BP, BMI and BC risk among men, we attempted to remove the influence of smoking by also studying people that had never smoked and to investigate BC taking into account its characteristics such as stage and grade. We found that BMI was linked with increased risk of superficial BC, and BP with more invasive BC.